"Delamination Plus": A Technique to Reduce Immediate Postoperative Diabetic Cavity Hemorrhage. Issue 3 (13th March 2023) - Tan, Shi Zhuan; Dell' aversana Orabona, Giancarlo; Robins, Julian J.; Kumaran, Neruban; Wong, Roger
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Purpose: To investigate the effectiveness of an intraoperative surgical technique to reduce the incidence of immediate postoperative cavity hemorrhage in patients undergoing vitrectomy for complications of proliferative diabetic retinopathy. Methods: A single-center, prospective study of 20 consecutive patients who underwent vitrectomy for proliferative diabetic retinopathy–related complications. A standard 3-port pars plana vitrectomy with either 23 g or 25 g was performed. At the end of surgery, the infusion was switched off to create transient hypotony and endolaser photocoagulation with long-duration burns were applied to actively leaking blood vessel. Results: The average age was 56.2 + 12.8 years. Eleven eyes had actively bleeding vessels at the end of surgery and received endolaser photocoagulation. No patients were found to have hypotony at Day 1 postoperative. Preoperative median visual acuity was 20/1, 600 improving to 20/40 at a median of 2.3 weeks post-op (range 0.4–8.5 weeks). Two eyes (10%) had a small postoperative cavity hemorrhage with 20/40 vision, which did not require further intervention. Conclusion: The described technique was found to be effective in reducing the incidence of postoperative cavity hemorrhage from up to 75% reported in literature to 10% in our pilot study. Further study with a larger number of patients is required.